Green behaviors towards intention to participate in river cleaning initiatives - Suhailah Shamsudin,; A.Aldrie Amir,; Nor Azilah Husin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
River pollution is one of the common environmental issues. In Malaysia, the Klang River is known as one of the highest-ranking rivers in the world contributing mismanaged plastic into the ocean, according to past researchers. In order to improve this situation, a non-structural approach in river conservation should be applied together with a structural approach. However, it will only be implemented successfully by the general public. This is because they play important roles in achieving river sustainability. By adopting green behaviors, the objective of this study is to predict the relationship between green self-efficacy (GSE) and green trust (GT) with the intention to participate in river cleaning initiatives. This study employs quantitative methods through a self-administered questionnaire. It involves 350 respondents from the Port Klang Area Fishermen's Association and the Selangor Recreational Boat Association (PBRS) who use the Klang River as their main route to the ocean. The respondents were randomly selected for the data collection process. The data was analyzed using SPSS to obtain preliminary data. The findings show that the reliability and validity of the instrument used is good and effective. GSE and GT have a relationship with the intention to participate in river cleaning initiatives. This study has the potential to provide information and understanding of human environmental behavior in addressing river pollution issues. Furthermore, it is anticipated that this study will serve as a crucial point of reference for scholars, authorities, and industry players in formulating holistic strategies and interventions that involve the general public to support sustainable river conservation.